Identification of the Mapping Models of the Players Cooperation in Serve Reception in Volleyball - Mazur, L. (Central European Journal of Sport Sciences and Medicine, 2021)
Introduction: Identifying cooperation in team games is a difficult process to implement. Thanks to the development of methods and techniques of game observation, it is possible to reliably and accurately identify and evaluate the actions of players. The collections of various analyzes are used to create pragmatic game models. There are several types of such models. The paper presents models representing effective cooperation in the game on the example of volleyball. Aim of the study: The aim of the study was to identify mapping models of effective cooperation in the game, in the game positioning phase - in the element of receiving-passing the ball (serves). The second goal was to present the differences and similarities between observed teams. Material and methods: The work uses a method called qualitative study of unique cases, the research material consists of the four highest-ranked teams from Rio de Janeiro 2016 Olympic Games. Results: Four different models of cooperation in receiving-passing the ball (serve) were identified. Each of them contains characteristic features visible in the figures. Conclusions: Various models of cooperation have been identified. Each team has a specific model of receiving-passing the ball (serve) due to the spatial flexibility. The models presented in the paper are effective because they show the cooperation of the best teams in the world.